Pengaruh Penggunaan Aplikasi Tiktok Terhadap Self-Esteem Remaja Perempuan di SMK Satria Dharma PerbaunganT.a 2024/2025 - Sari, Nadia Puspita; Asyah, Nur; Hidayati, Dina; Syaimi, Khairina Ulfa (Indonesian Journal on Education (IJoEd), 2025)
The purpose of this study was to determine the Effect of Using the Tiktok Application on Self-Esteem of Female Adolescents at SMK Satria Dharma Perbaungan. This research is a quantitative research with a descriptive approach. The population in this study were all female students at SMK Satria Dharma Perbaungan. The sample of this study was 36 students who were taken as samples taken using a purposive sampling technique whose criteria used in this study were female. The results of this study are that the level of use of the Tiktok application by female adolescents at SMK Satria Dharma Perbaungan can be said to be high. This was obtained from the results of the adolescent questionnaire with details of 40% with a frequency of 14 adolescents out of 36 respondents in the high category. Furthermore, the self-esteem of female adolescents at SMK Satria Dharma Perbaungan can be said to be moderate. This was obtained from the results of the student questionnaire with details of 37.5% with a frequency of 15 adolescents out of 36 respondents in the low category. The results of the simple linear regression analysis showed that there was a significant influence between the use of the Tiktok application on the self-esteem of female adolescents at SMK Satria Dharma Perbaungan. The model summary table shows an R Square value of 0.723. This value indicates that the contribution of the Tiktok application usage variable to self-esteem is 72.3%. While the remaining 27.7% is influenced by other factors outside the Tiktok application usage variable. Based on the regression coefficient value of X of 2.936, it states that for every 1% increase in the value of Tiktok application usage, the self-esteem value will also increase by 2.936. This means that the higher the level of Tiktok application usage, the lower the level of self-esteem of female adolescents at SMK Satria Dharma Perbaungan.